ANALISIS KINERJA BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN PENDAPATAN DESA DI DESA PULAU PANDAN KECAMATAN LIMUN KABUPATEN SAROLANGUN - Yuliana, Deresty (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2024)
This study on the analysis of the performance of village-ownedenterprises (BUMDES) Pandan Island aims to determine how todetermine how the effectiveness of the performance of BUMDESto increase the income of the village “Pandan Island”. This studyuses qualitative descriptive method. Informants were taken bymeans of purposeful samples and research data obtainedthrough research data obtained through secondary data,observation, and in-depth interviews. The results showed thatBUMDES "Pandan Island" has set the price of subsidized fuelwhich in this case is 3 Kg LPG Gas. However, the practice thatoccurs in the field has not been in accordance with what iswanted because even though BUMDES have set the selling priceof 3 Kg LPG Gas, there is still a frequent scarcity of 3 Kg LPG Gasamong the community. This is due to the lack of supervision ofBUMDES to people who want to buy gas so that subsidized fuelseems to be less on target. Which should be reserved for peoplewho have a lower middle economy to be better. In this problem,BUMDES must improve a lot, especially looking for solutions sothat there is no longer a shortage of subsidized fuel supplyamong the community and BUMDES must improve, especiallyin the supervisory function in order to encourage thecommunity's economy to be better.